India and Trade Facilitation in Services (TFS) Agreement: Concerns and way forward - Arpita Mukherjee; Avantika Kapoor (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Services are a major component of global gross domestic product and employment, and a rising component of global trade and investment flows. This is the largest sector of the Indian economy contributing significantly to economic growth and foreign investment flows. India is among the top ten World Trade Organization member countries in trade in services, and the country has a positive trade balance in services. However, global trade in services faces a number of barriers at the border and behind the border, which makes it difficult for service providers from developing countries such as India to access key markets in their preferred modes of services trade. Given this background, this paper examines how trade in services can be liberalised within the WTO framework. It presents some of the recent estimates of trade costs related to barriers to trade in services, and examines why it is difficult to measure trade facilitation in services. It then examines India's proposal on Trade Facilitation in Services (TFS), highlighting the benefits, gaps in the proposal, issues and way forward. The paper is based on secondary information analysis, and discussion with policymakers and experts from India and abroad.
Keywords: F1; F2; 330; services; trade facilitation; trade costs; trade agreements; WTO; India